Ketepatan Waktu dan Okupansi Terhadap Kinerja Kereta Api Joglosemarkerto - Usri Jati Hastuti; Masjraul Hidayat; M. Iqbal Firdaus (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of the study are to analyse the train’s punctuality and load factor and to verify the effect of the train’s punctuality to its load factor. The study is about the Joglosemarkerto rail transport for 62 days or 2 months from December 2018 to Januari 2019. The data used in this study was a secondary data based on the delay and load factor of daily departure of the rail transport. The data analysis were using two techniques which were descriptive quantitative and linear regression. The result shows that the negative effect of punctuality to load factor due to the delay that giving negative effect to the load factor. The equation from the effect of punctuality to load factor was shown in Y = 310,790 – 1,630X.